English-Indonesian Translation Method of Book’s Glossary - Xirera, Hastin; Abdul Muth'im; Nasrullah, Nasrullah (New Language Dimensions, 2021)
Translation is an adjustment idea of one language to a different language equitably. In doing a translation, a translator needs to apply some methods to produce an acceptable translation. Plenty of researches on translation method have been administered. However, translation method research on a book's glossary is ostensibly still under-researched in translation studies. So that, to fill in this gap, this research aimed at figuring out and describing the methods of English-Indonesian translation used in the book's glossary “An Introduction: Theories of Learning 7th Edition Book”. This research exerted a qualitative method. The objects of this research were An Introduction: Theories of Learning 7th Edition Book and its Indonesian version Theories of Learning: Teori Pembelajaran Edisi ke-7 based on Newmark’s translation methods. The data was geared by documentation. Afterward, the researchers classified the data suited to the determined table of instrument as researchers' tools in data collection. Furthermore, after elaborating the data, researchers analyzed it descriptively. The result showed that there were five out of eight translation methods applied by the translator. Three of them are concentrated on source text comprising semantic translation, literal translation, and faithful translation. While two of those are concentrated on target text, namely free translation and communicative translation.